Pengaruh Penggunaan Media Buku Cerita Bergambar terhadap Kemampuan Berbahasa Anak Usia Dini - Rahyana Hasibuan; Deby Amanda; Rani Astria Silvera Harahap (Information Technology and Science (ITScience), 2026)
The objectives of this study were to determine: (1) the language ability of early childhood students at TK Palahy, and (2) the effect of using picture story books on the language ability of early childhood students at TK Palahy. This research employed a quantitative approach with an experimental design. The research design applied was a pre-experimental type, namely one-group pretest-posttest. The instruments used consisted of observation, documentation, and oral tests. Data analysis techniques involved descriptive statistics as well as prerequisite tests, including normality and homogeneity tests. Hypothesis testing was carried out using the paired sample t-test. The results of the study showed that: (1) the development of children's language ability at TK Palahy, Roburan village, had improved well. This was evident from the results of the observation on children's language ability during the pretest and posttest. The average score obtained in the pretest was 21, while in the posttest it increased to 38.58. (2) The results of the hypothesis test using the paired sample t-test obtained a tcount of 37.64. Compared to the ttable at a 95% confidence level or 5% significance level with a degree of freedom (df) = n-2 = 24-2 = 22, the ttable value was 1.717. Since tcount (37.64) > t table (1.717), it can be concluded that Ha is accepted and Ho is rejected. This means that there is a significant effect of using picture story books on the language ability of early childhood students at TK Palahy, Roburan village.